Documenting adaptation strategies for building up climate resilient inland fisheries practices in developing countries: Status, synthesis and overview - Sarkar, Uttam Kumar; Suchismita Saha, Suchismita Saha; Puthiyottil, Mishal; Karnatak, Gunjan; Ghosh, Bandana Das; Lianthuamluaia, Lianthuamluaia; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2021)
The inland fisheries resources are greatly affected by the anthropogenic activities, which are aggravated by climate change. The rapid degradation of these ecosystems has led to decline in their fisheries across the globe. Implementation of suitable mitigation and adaptation strategies is essential to cope up with the deleterious impacts and to enhance resilience of ecosystems and adaptive capacity of fishers. The present communication discusses impacts of climate change on inland fisheries and documents climate smart adaptation strategies adopted by different countries across the globe. The article also discusses strategies adopted in wetlands of eastern India to enhance adaptive capacity of fishers against climate change stress. The degree of effectiveness of mitigation and adaptation activities depends on the impacts at temporal and spatial scale and strategic planning. The present communication reviews the status of different adaptation strategies identified, documented and adopted by various countries, mainly the developing countries in order to mitigate the loss of fisheries from extreme events and climatic variability.Key words Climate change, Inland fisheries, Adaptation strategies, Climate smart fisheries